Empirical Correlations for K-Values of Crude Oils - Jose V. Flores-Cano; Carlos G. Aguilar-Madera; Erik C. Herrera-Hernández; G. Espinosa-Paredes; Jose P. Ruelas-Leyva; Victor Matías-Pérez; Jorge A. Briones-Carrillo (International Journal of Chemical Engineering)
Based on the Soave–Redlich–Kwong equation of state, empirical correlations for the K-values of N2, CO2, H2S, C1, and C2 are proposed. Complementarily, the binary interaction coefficients involving the plus fraction, C7+, were optimized by fitting into 131 experimental data from the literature. The criterion to select the form of the empirical correlations was based on the identification of the major dependencies of the equilibrium constants on the system variables (e.g., pressure, temperature, and composition). For most of the experimental data, the saturation pressure calculated via the empirical correlations is in excellent agreement with those reported from the laboratory. The empirical correlations cover a variety of temperatures (128–314°F), pressures (313–6880 psi), and compositions (N2: 0.0–1.67%; CO2: 0.0–9.11%; H2S: 0.0–3.68%; C1: 5.63–74.18%; C2: 0.84–12.45%; C7+: 10.72–83.2%). The proposed correlations are useful for rapid vapor-liquid equilibrium calculations during the compositional modeling of petroleum reservoirs.